The Influence of Smart Box Learning Media on Students' Social Studies Learning Outcomes in Class IV State Elementary School 091273 Karang Bangun - Nadapdap, Titin S.; Thesalonika, Emelda; Napitupulu, Rio Parsaoran (MSJ : Majority Science Journal, 2025)
This study aims to determine the effect of Smart Box learning media on the social studies learning outcomes of grade IV students at Sd Negeri 091273 Karang Bangun.This research is a quantitative research with an experimental research method. The research design used is Pre-Experimental Designs, it is said to be Pre-Experimental Designs because this design is not yet a real experiment because there are still external variables that influence the formation of the dependent variable. This research was conducted at SD Negeri 091273 Karang Bangun which is located at JL. Rajamin Purba, SH, Siantar District, Simalungun Regency, North Sumatra Province. This research will be conducted in the even semester of the 2024/2025 academic year. In quantitative research, the data analysis technique used is clear, namely directed at answering the problem formulation or testing the hypothesis that has been formulated in the proposal. In accordance with the results of the research that the researcher has conducted, the researcher can conclude that there is an influence of Smart Box media on the social studies learning outcomes of Class IV students of SD Negeri 091273 Karang Bangun. This can be proven from the learning outcomes of students before being given treatment, namely 2 students had achieved the KKTP score and 22 students had not achieved the KKTP score and after being given treatment, the learning outcomes of students increased, namely 23 students had scores above the KKTP and 1 student below the KKTP. Based on the results of the hypothesis test that has been carried out using SPSS version 24, it was obtained tcount = 21.142> ttable = 1.711 and significant (2-tailed) = 0.00 <0.05. From these results Ha is accepted, it can be concluded that there is an Influence of Smart Box Media on the Social Studies Learning Outcomes of Class IV Students of SD Negeri 091273 Karang Bangun in the 2024/2025 Academic Year